Fabrication of PANI/GO/Pd nanocomposite based tapered optical fiber for hydrogen gas sensing applications - Alkhabet, Mohammed M.; Girei, Saad H.; Farhan, Ammar Hatem; Altalebi, Omar; Al-Isawi, Zaid Khalaf; Khalaf, Ahmed L.; Jaafar, Jaafar A.; Yaacob, Mohd H. (Elsevier Ltd, 2024)
Hydrogen (H2) is viewed as a promising solution for future energy demands because of its effectiveness, widespread availability, environmentally friendly properties, and sustainability. The study focuses on developing and evaluating H2 gas sensors based on optical fiber coated with nanocomposites such as polyaniline (PANI), graphene oxide (GO), and palladium (Pd) as sensing layers. An optical transducing channel was developed using a 125 μm diameter multimode optical fiber to improve the light field. The optical fiber was reduced to 20 μm and coated with the PANI/GO/Pd nanocomposite using drop casting. The proposed optical fiber sensor achieved a sensitivity of 9.79/vol%. The response and recovery time were calculated at room temperature and found to be 60 and 190 s, respectively. Overall, the developed optical fiber sensor shows high stability and excellent selectivity to H2 gas when compare to other gases such as NH3 and CH4.